EFFECTS OF IMIDACLOPRID APPLICATION ON ANTIOXIDANT SYSTEM IN SUNFLOWER LEAVES - Kirecci, O. A.; Kustili, Y.; Lirmizikaya, A. G.; Ozsahin, D. (Aloki Applied Ecological Research and Forensic Inst Ltd, 2024)
Imidacloprid, one of the latest members of the neonicotinoids, is a widely used synthetic organic insecticide. In this study, it was aimed to reveal the effects of 2 ppm, 4 ppm, and 8 ppm imidacloprid on antioxidant enzymes and lipid peroxidation in Helianthus annuus L. Tarsan-1018 oilseed sunflower leaves. As a result of the applications, sunflower leaves were collected and frozen in liquid nitrogen, then stored at-40 degrees C until analyses were conducted. Sunflower seeds were a registered variety and were obtained from Trakya Agricultural Research Institute. Imidacloprid were applied as foliar to the Sunflower plant grown under controlled conditions and samples were taken at 24. 48. and 72. hours. Superoxide dismutase (SOD), catalase (CAT), glutathione s-transferase (GST), glutathione (GSH), oxidized glutathione (GSSG) and malondialdehyde (MDA) analyzes were performed in the samples taken after the applications. As a result, it was determined that imidacloprid had different effects on the biochemical parameters of sunflower plant leaves. It was understood that imidacloprid used in ppm doses stimulated antioxidant defense and created stress responses in the plant, and as with all plant protection products, the importance of proper dosage and controlled use must not be overlooked.
Keywords: antioxidant; enzyme; Helianthus annuus; oxidative stress; pesticide